Resistance and Representation: The Making of Chinese Identity in the Art of the Yiyanhui and the Equator Art Society in 1950s Singapore - Emelia Ong Ian Li (Wacana Seni Journal of Arts Discourse, 2020)
This paper examines the social realist paintings of the art groups Yiyanhui and the Equator Art Society which emerged during the 1950s in Malaya and Singapore. Their works centred on the social functions of art and its subject matters featured the working class, the Japanese occupation and anti-British colonial sentiment. Their artworks are viewed here as cultural productions shaped by the negotiation between dominant-subordinate relationships within a postcolonial framework. It is argued that the artistic productions examined here may be viewed not only for its overarching “social realist” endeavours but, also as a struggle to rewrite the narrative of the Chinese in Malaya against of the prevailing static representations forwarded by the colonial campaign. The first part of the paper illustrates how colonial discourse in the local press propagated an image of the Chinese as inherently susceptible to communism, untrustworthy, and opportunistic. The second part of the paper shows how the artists resisted this essentialist image of Chinese identity and offered a more complex picture of a Chinese-Malayan identity. Through a combination of interviews, written artist’s statements, formal and contextual considerations of the artworks, as well as a cultural studies framework, the author demonstrate how a different narrative is being offered by these artists through two related processes in identity construction: qualifications for authenticity and belonging, the articulation of ambivalence. Resistance thus, is explored as encompassing a network of strategies employed by these artists as a way to reject colonialist representations of otherness and gain authorial agency against the intellectual and ideological dominance of colonial discourse.